Formation of wheat bread quality indicators when adding pulmonaria mollis extract (Pulmonaria mollis) - L. Z. Borieva; A. Ya. Tamakhina; A. A. Akhkubekova (Новые технологии, 2019)
Wild plants with proven therapeutic and prophylactic properties play an important role in the production of functional and enriched bakery products. The article presents the results of studies on the effect of Pulmonaria mollis extract (Pulmonaria mollis Hornem.) on the quality of wheat bread. P. mollis plant contains (in terms of absolutely dry matter) 1.86% of flavonoids, 10.95 % of polysaccharides, 256.34 μg / g of iron, 33.47 μg / g of manganese, 15.07 μg / g of copper and 42.92 μg / g of zinc. During the experimental baking, Pulmonaria mollis extract was added to the dough in the concentration of 2.5; 5.0; 7.5; 10.0 and 12.5 %.The dough was prepared in a single-phase (straight) way. The introduction of P. mollis extract into the dough formulation led to the acceleration of acid accumulation, a decrease in the dough fermentation duration and proofing of dough pieces. The 10% concentration of P. mollis extract was selected as an optimal variant of wheat bread formulation. In this case a 11.02 % increase in bread porosity and 0.32 cm3 / g increase in specific volume were noted, as well as an improvement in the state of the surface and structure of porosity. Wheat bread with P. mollis extract has functional properties and is recommended for the prevention of iron deficiency conditions.